2011
DOI: 10.1111/j.1365-2621.2011.02594.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterisation of β‐cyclodextrin crosslinked by adipic acid

Abstract: This study was conducted to investigate the structural characterisation of b-cyclodextrin (b-CD) crosslinked by adipic acid. b-CD was treated with different concentrations (0%, 5%, 10% and 15%, w ⁄ v) of adipic acid. Different instruments, such as scanning electron microsope (SEM), Fourier-transform infrared (FT-IR) spectroscopy and 1 H and 13 C nuclear magnetic resonance (NMR) spectra were used to find out chemical structure in the crosslinked b-CD. SEM analysis suggested that crosslinking b-CD with 15% adipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…However, higher the cross‐linking at the level of 15% favours the greater removal of cholesterol from milk and cream, and can easily separate out from cholesterol at ten repeated times. Kwak et al. (2011) also reported that the addition of adipic acid at higher level (15%) favoured more cross‐linking of hydroxyl groups of β‐CD and carboxyl groups of adipic acid which can be visualised by the intensive absorption band at 1706 cm −1 by FT‐IR spectroscopy.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…However, higher the cross‐linking at the level of 15% favours the greater removal of cholesterol from milk and cream, and can easily separate out from cholesterol at ten repeated times. Kwak et al. (2011) also reported that the addition of adipic acid at higher level (15%) favoured more cross‐linking of hydroxyl groups of β‐CD and carboxyl groups of adipic acid which can be visualised by the intensive absorption band at 1706 cm −1 by FT‐IR spectroscopy.…”
Section: Resultsmentioning
confidence: 89%
“…Lower cross‐linking may leads to a breakdown of cross‐linking in repeated reusability. Kwak et al. (2011) reported that a lower level (0–5%) of adipic acid cross‐linked β‐CD shows almost no absorption band at 1706 cm −1 in FT‐IR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Animal foods such as meat and dairy products contain high saturated fats and cholesterol which may cause the elevation of blood cholesterol [15]. Thus, it has been recommended that fat content should be no more than 30% of the diet, and also less than one-third of dietary fat should be saturated fat [16].…”
Section: Introductionmentioning
confidence: 99%